Pengaruh Inflasi, BI 7-Day Reserve Repo Rate, Dana Pihak Ketiga, Dan Fee Based Income Terhadap Profitabilitas BNI Syariah Tahun 2015-2020 - Badi' Rizqi Aminulloh; Dedi Suselo (Prodi Perbankan Syariah FAI UMT, 2021)
This study was find out and conducted the effect of variables macro economics and source of income funds on profitability of BNI Syariah, with inflation, BI 7-day reserve repo rate, third party funds and fee based income as a research variable. The population in this study is a monthly financial statements of BNI Syariah in 2015-2020. The sample was determined by a purposive sampling method – 68 samples. The method used in this research is descriptive method with quantitative approach. The data used in this research is in the form of monthly financial statements that have been published by BNI Syariah (Persero) Tbk as well as data published by Bank Indonesia. The data test techniques in this study used normality test, multicolinearity test, heterocysticity test, autocorrelation test, multiple linear analysis and determination coefficient. The results of this study stated that partially inflation and BI 7-day reserve repo rate have no significant effect on profitability of BNI Syariah (Persero) Tbk. While the variables of third party funds and fee based income partially have a positive significant effect on profitability of BNI Syariah (Persero) Tbk for the period 2015 until 2020